Ecological studies of aquatic moss pillars in Antarctic lakes 1. Macro structure and carbon, nitrogen and Chlorophyll a contents - Kudoh, Sakae; Tsuchiya, Yasutaka; Ayukawa, Eri; Imura, Satoshi; Kanda, Hiroshi (National Institute of Polar Research, 2003)
P(論文) Structures of a typical 'moss pillar' submerged in Antarctic lakes were investigated to analyze the sizes, age distribution, and composition such as shoot density, dry weight, carbon, nitrogen and chlorophyll a using a sample collected from lake B-4 Ike in the Skarvsnes region, East Antarctica. The moss pillar was mainly composed of shoots of a moss species, Leptobryum sp. Most of the green shoots of the species were located at the top surface of the pillar, and brownish old shoots with prominent vegetative diaspores, so-called rhizoidal tubers, formed the internal body of the pillar. The internal core of the pillar was nearly empty, and seemed to be decomposed considerably. Dry weight, carbon, nitrogen and chlorophyll distributions in the pillar took heterogeneous patterns, that is, they were largely centered at apical parts. It is suggested that growth of the moss pillar occurred extensively at the apical part. The age was estimated ca. 250 years at ca. 20 cm below the apical top by the AMS method. The presence of the moss pillar in lake B-4 Ike indicates that a tremendous amount of biomass has been produced under the oligotrophic freshwater Antarctic lake environment over more than a quarter millennium. departmental bulletin paper